2000
DOI: 10.2116/analsci.16.429
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Elution and Determination of Uranium and Vanadium Adsorbed on Amidoxime Fiber from Seawater

Abstract: Uranium is one of the most valuable metals in seawater. Various inorganic and organic adsorbents for the recovery of uranium in seawater have so far been synthesized and evaluated. [1][2][3][4] Among the adsorbents reported, amidoxime polymers are noted as being the most promising. 1,3,4 Hirotsu et al. 5,6 have already investigated a separative elution of uranium from an amidoxime polymer which had been immersed in seawater, and proposed the selective elution of uranium from an amidoxime polymer with 0.5 or 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 4 publications
4
85
0
Order By: Relevance
“…A comparative evaluation was made to see the uranyl ion adsorption capacity of various adsorbents developed by different groups and the new adsorbent developed by our group. Adsorbent systems listed in Table 1 include only those based on et al [25] Lightly cross-linked poly(acrylonitrile-co-divinylbenzene) 0.650 mg/g U 0.65 mg/g Suzuki d et al [26] Polypropylene nonwoven fabric grafted with acrylonitrile and methacrylic acid 0.576 mg/g U 1.8 mg/g V 0.576 mg/g U 1.8 mg/g V Kawai e et al [14] Polypropylene fiber cografted with methacrylic acid and acryloylchloride…”
Section: Resultsmentioning
confidence: 99%
“…A comparative evaluation was made to see the uranyl ion adsorption capacity of various adsorbents developed by different groups and the new adsorbent developed by our group. Adsorbent systems listed in Table 1 include only those based on et al [25] Lightly cross-linked poly(acrylonitrile-co-divinylbenzene) 0.650 mg/g U 0.65 mg/g Suzuki d et al [26] Polypropylene nonwoven fabric grafted with acrylonitrile and methacrylic acid 0.576 mg/g U 1.8 mg/g V 0.576 mg/g U 1.8 mg/g V Kawai e et al [14] Polypropylene fiber cografted with methacrylic acid and acryloylchloride…”
Section: Resultsmentioning
confidence: 99%
“…Thus it is suggested that PANSIL is also able to act as a ligand to neutral uranyl species. Such behaviour is not unexpected as amidoxime fibres have been shown to preferentially adsorb uranium from seawater [17], which has a pH of ~8.…”
Section: +mentioning
confidence: 91%
“…Suzuki et al 19 demonstrated that significant amount of Vanadium was adsorbed alongside the uranium by amidoxime polymers. To extract Vanadium and free the adsorbent functional groups, the concentration of the hydrochloric acid elution solution has to be increased by almost two orders of magnitude compared to what is necessary for uranium extraction 19 .…”
Section: Fig 3 Adsorbent Degradationmentioning
confidence: 99%
“…To extract Vanadium and free the adsorbent functional groups, the concentration of the hydrochloric acid elution solution has to be increased by almost two orders of magnitude compared to what is necessary for uranium extraction 19 . It is therefore likely that most of the elution damage comes from the removal of Vanadium.…”
Section: Fig 3 Adsorbent Degradationmentioning
confidence: 99%